The complete mitochondrial genome sequence of the Tibetan red fox (Vulpes vulpes montana). (3rd September 2015) - Zhang, Jin; Zhang, Honghai; Zhao, Chao; Chen, Lei; Sha, Weilai; Liu, Guangshuai
Abstract: In this study, the complete mitochondrial genome of the Tibetan red fox ( Vulpes Vulpes montana ) was sequenced for the first time using blood samples obtained from a wild female red fox captured from Lhasa in Tibet, China. Qinghai--Tibet Plateau is the highest plateau in the world with an average elevation above 3500 m. Sequence analysis showed it contains 12S rRNA gene, 16S rRNA gene, 22 tRNA genes, 13 protein-coding genes and 1 control region (CR). The variable tandem repeats in CR is the main reason of the length variability of mitochondrial genome among canide animals.